Prevalence of Plasmodium falciparum chloroquine resistant gene markers, pfcrt-76 and pfmdr1-86, eight years after cessation of chloroquine use in Mwea, Kenya - Sabah Ahmed Omar,1 Francis W. Makokha,2,3 Fat'hia Abdo Mohammed,1 Francis T. Kimani,1 Gabriel Magoma3 (The Journal of Infection in Developing Countries, 2007)
Background and Methodology: The prevalence of T76 and Y86 Plasmodium falciparum molecular markers for chloroquine (CQ) resistance in the Pfcrt and Pfmdr1 genes were investigated by PCR-RFLP and dot blot analysis in samples (50 for Pfcrt and 51 for Pfmdr1) collected in May 2005, eight years after chloroquine (CQ) cessation.Results: Our findings show that 94% of field isolates from this site still harbor T76 mutation in Pfcrt while 6% have the wild type allele K76 [T test, P=0.04058 (1997 versus 2005)]. Dot blot analysis revealed that most of the isolates had MET polymorphism at position 74, 75 and 76 wild type allele of the Pfcrt gene. When Pfmdr1-86 was analyzed by dot blot, 6% of the isolates had wild type allele N86, 73% had mutant allele Y86, and 21% had both N and Y [T test, P=0.04058 (1997 versus 2005)]).Conclusions: Dot blot hybridization was found to be more sensitive and specific than PCR-RFLP. The study showed a moderate reversal to sensitivity by the P. falciparum population in the study site compared to the situation before CQ cessation.